Comparison of Most-to-Least Prompting to Flexible Prompt Fading for Children with Autism Spectrum Disorder. Issue 2 (2nd April 2016) - Leaf, Justin B.; Leaf, Jeremy A.; Alcalay, Aditt; Kassardjian, Alyne; Tsuji, Kathleen; Dale, Stephanie; Ravid, Daniel; Taubman, Mitchell; McEachin, John; Leaf, Ronald
ABSTRACT: This study compared most-to-least prompting to flexible prompt fading for teaching four children with an autism spectrum disorder various expressive tasks. Using a parallel treatment design nested into a multiple probe design, researchers taught each participant how to expressively label six pictures with most-to-least prompting and six pictures with flexible prompt fading. The researchers evaluated effectiveness, maintenance, efficiency, and performance across both prompting conditions and across all participants. Results indicated that both prompting procedures were effective across all four participants. Results also indicated that flexible prompt fading led to a higher percentage of independent correct responding during teaching trials. For three of the participants, flexible prompt fading was also a more efficient procedure. Results were mixed in terms of maintenance across the four participants.